Undoing structural racism in dentistry: Advocacy for dental therapy. (11th January 2022) - Bianchi, Tera; Wilson, Kasey; Yee, Albert
Abstract: Like other areas of health, structural racism has a deep impact on oral health and is a key driver of racial inequities in access to care and outcomes. Racism also structures the relationship between oral health and access to economic opportunities. As a result, communities of color, American Indian/Alaska Native (AI/AN) communities, and low‐income populations experience the highest rates of the health, social, and economic costs of dental disease. This is compounded by issues of community‐level dental fear/trauma resulting from receiving itinerate care. Dentistry has long struggled to equitably distribute care and diversify its overwhelmingly white and affluent workforce, resulting in many communities not having access to providers who represent their identity and/or live in their community. While multi‐generational lack of access to dental care is not unique to Alaska, Alaska Native communities are the home to a reimagined, community‐centered care delivery system that is improving health outcomes. For almost two decades, AI/AN leaders have recruited and trained community members to serve as dental therapists—dental team members who offer routine and preventive care responsive to local geographic and cultural/community norms. As members of the communities they serve, dental therapists are fluent in the language and cultural norms of their patients, improving patient‐provider trust, access to care, and oral health outcomes. The communities that dental therapists serve are also now investing money and training in their community members, building educational opportunities, and professional wage jobs and directly countering the economic impact structural racism has on oral health.